Identifying Students learning Styles as a Way to Promote Learning Quality - Jafar Sadegh Tabrizi; Omeleilan Alizadeh; Hossein Koshavar (Tabriz University of Medical Sciences, 2013)
Introduction: The major part of peoples knowledge, skills and abilities are achieved during the complex process called learning. Learning is not simply the product of mere intelligence and capabilities of individual; it also depends on other factors such as personality traits, personal interests, and t ype of duty and di fferent methods and st yles. The understanding of each individual fits with his/her learning style. The aim of this study was to determine the learning st yles of Health Care Management students in Tabriz University of Medical Sciences. Methods: Learning styles of 55 Health Services Management students in Tabriz Health and Nutrition Faculty were evaluated in 2009 using a twelve-question Kolb questionnaire in a descriptive study. The data was anal yzed using SPSS. And the frequency of students learning styles was identified by their ages and averages. Results: In this study, 69% of the students were female and the dominant learning method was Assimilator (42%). Other styles with a regard to their frequency were Diverge (24%), Coverage (22%)and Accommodator (12%). In the present study,no statistically significant relationship was found in learning styles between the gender (p= 0.644)and average (p = 0.676)of the students. Conclusion: Assimilator and Diverge methods were the most common ones among the management students. Hence, to improve the quality of learning in this group of students, it is proposed that the teachers use interactive and creative teaching methods such as small and la rge group discussion,brain storming, problem solving, debate-based learning, self-learning and lecturing.